Why WFOEs is becoming more and more popular in China? - Liu, Lei (2008)
The following study seeks to identify the possible reasons that why more and more foreign companies establish WFOEs rather than Joint Venture. To identify research a framework and get proper conclusion for the research, this dissertation reviews lots of various theories of FDI, entry mode, etc. Retail industry has been selected as case study to explain what impacts affect this change happen. The research method of this dissertation is case study. There are two cases which are P&G and Carrefour has been discussed to address the reasons why there is such a trend among foreign companies in China. The key findings are many foreign companies have met lots of problems in JV, it is due to different culture, management style, interests, etc. Further more, they have learnt enough knowledge to go to alone so that they could feel more freedom to make decision of strategy and make more profits. In addition, some Chinese partners do not support enough to foreign companies in JV, these make foreign companies disappointed. The conclusion is about give findings and gives the recommendation for policy of trading, and for local Chinese partners how to face such challenge.